Book Review: Doing Ethnographic Research Online - Anak Agung Gde Satia Utama (Fakultas Seni Rupa dan Desain ITB, 2023)
In the field of consumer and marketing research, netnographies have become a widely accepted form of research. Our social worlds are going digital, with perhaps hundreds of millions of people interacting through various online communities and their associated cybercultures. Netnography is a form of ethnographic research adapted to the unique contingencies of computer-mediated social interaction. This book aims to provide a set of methodological guidelines, a disciplined approach to the culturally—oriented study of that technologically—mediated social interaction that occurs through the Internet and related information and communications technologies. The methods that these various fields have used to investigate these topics are still somewhat uncertain and in flux. Most of this type of work written after the term was coined uses the guidelines and techniques that have been published about the netnographic approach.